Mate-choice for close kin is associated with improved offspring survival in Lodoicea maldivica, the largest-seeded plant in the world - Morgan, Emma J.; Kaiser-Bunbury, Christopher N.; Edwards, Peter J.; Fleischer-Dogley, Frauke; Kettle, Christopher J. (Nature Portfolio, 2023)
We studied spatial patterns of kinship in the offspring of the endangered Lodoicea maldivica, a dioecious palm that produces the largest seed of any plant. Previous research has suggested that restricted seed and pollen dispersal in populations resulted in strong spatial genetic structure. We used microsatellites to genotype young plants and their potential parents at four sites across the species’ entire natural range. We determined the most likely parents of each young plant based on the spatial separation of each parent pair, their genetic relatedness, and the level of correlated paternity. We identified both parents (43 female, 54 male) for 139 of 493 young plants. Mean distance between parental pairs was 26.8 m. Correlated paternity was low (0.168), indicating that mother trees were often pollinated by several fathers. Parental pairs were more closely related than expected by chance, suggesting outbreeding depression. Our results highlight the apparent strong mate choice for close kin in parent pairs of surviving offspring. We discuss the alternative biological processes that could lead to this, including the potential for break-up of favourable allelic combinations necessary for the development of the palm’s very large seed. Management implications include germinating seeds where they naturally fall, using a diverse range of male plants as pollen donors for hand pollination, and protecting the native community of gecko pollinators.